Biotechnological approaches for the production of prebiotics and their potential applications. (December 2013) - Panesar, Parmjit S.; Kumari, Shweta; Panesar, Reeba
Abstract : Worldwide interest in prebiotics have been increasing extensively both as food ingredients and pharmacological supplements, since they have beneficial properties for human health. Prebiotics not only stimulate the growth of healthy bacteria such as bifidobacteria and lactobacilli in the gut but also increase the resistance towards pathogens. In addition to this, they also act as dietary fiber, an energy source for intestinal cells after converting to short-chain fatty acids, a stimulator of immune systems, sugar replacer etc. Moreover, due to heat resistant properties, they are able to maintain their intact form during the baking process and allow them to be incorporated into every day food products. Thus, they can be interesting and useful ingredients in the development of novel functional foods. This review provides comprehensive information about the different biotechnological techniques employed in the production of prebiotics and their potential applications in different areas.